TINJAUAN SISTEM MONITORING DAN MANAJEMEN PERAWATAN MESIN KAPAL : INTEGRASI TEKNOLOGI DIGITAL DAN PENDEKATAN PREDIKTIF: REVIEW OF SHIP ENGINE MAINTENANCE MONITORING AND MANAGEMENT SYSTEMS: INTEGRATION OF DIGITAL TECHNOLOGY AND PREDICTIVE APPROACHES - PURBA, IVANA BULAWANTA; PUTRA, HAIKAL AULIANSYAH; DA CRUZ, LEONIO SOARES (PT Yupin Felicitas Utama, 2025)
Ship engines are a vital component in maintaining the safety, efficiency, and reliability of shipping operations. The main problems faced are sudden breakdowns due to delayed maintenance and limited engine condition monitoring. This study aims to review national and international literature related to ship engine monitoring and maintenance management systems. The method used was a systematic literature review of 10 scientific articles, consisting of 7 national journals and 3 international journals. The results indicate that national research focuses primarily on designing IoT-based monitoring systems, digitizing engine data, and implementing Reliability-Centered Maintenance (RCM). Meanwhile, international literature emphasizes the application of predictive methods based on artificial intelligence, vibration analysis, and machine learning for condition-based maintenance. Future research recommendations include the integration of IoT with artificial intelligence to support efficient ship engine maintenance in Indonesia. Keywords: Ship Engine, Monitoring System, Predictive Maintenance, Lot, Maintenance Management